Abraham Maslow's Hierarchical Need Fulfillment and Herzberg's Two-Factor Theory for Creating Worker Loyalty - Artaya, I Putu; Kamisutara, Made; Muchayan, Achmad; Deviyanti, IGA Sri (LPPM of NAROTAMA UNIVERSITY, 2021)
This research was conducted in an attempt to identify and analyze the role and influence of two universally applicable theories in the life of an employee when working in a company. The research subjects are employees who work at the bank. The data collection model is carried out primarily using a questionnaire to explore their perceptions in creating and or maintaining a sense of loyalty in their workplace. To prove this, the researchers chose a bank that has been around for a long time, where there are 25 employees. We want to know whether Maslow and Herzberg's theory of motivation remains universally applicable in their work environment. This research is an associative study using the primary data base, this data from interviews and filling out questionnaires from the bank employees. Measurement of data using ordinal data with a Likert scale approach. From the results of filling out the questionnaire, the percentage results obtained that 71.4% of them tend to agree on the existence of their existence and fulfill their needs hierarchically. Through associative analysis, it can be obtained that the physiological results are 49.1% well fulfilled, sense of security is 47.4% fulfilled, social 43.8% is fulfilled, self-esteem 72.5% is fulfilled, and self actualization is 49.1% also fulfilled in the bank, this condition is enough to make their employees loyal in contributing energy, time and thoughts. Overall 93.7% of Maslow's hierarchical needs and Herzberg's maintenance are able to create a sense of employee loyalty to the workplace. The fulfillment of 72.5% hierarchical needs is dominated by the fulfillment of self-esteem, then in terms of maintenance theory, Herzberg is dominated by self-esteem and self-actualization